Mengembangkan Kecerdasan Logika Matematika Anak Melalui Permainan Harta Karun Geometri Pada Kelompok B Di TK Aisyiyah Bentangan Wonosari Klaten Tahun Ajaran 2015/2016 - Munfi'atun Putri, Asri, Ilham Sunaryo, M.Pd.AUD (2016)
The purpose of this research is to increase the children's mathematic logic intelligence through treasure game at TK Aisyiyah Bentangan Wonosari Klaten on 2015/2016 academic year. The subject of this research is group B students of TK Aisyiyah Bentangan Wonosari Klaten, at least 25 students. This research is an action research which collaboratively with the teacher. This research uses Suharsini Arikunto design model. The method of collecting qualitative data in this research is through the observation, interview. The technique of analyzing data is comparative analizye. This research shows that the increasing of the children's mathematic logic in TK Aisyiyah Bentangan Wonosari Klaten at 2015/2016 academic year before doing this research, their abilities are just 47,80%. After doing the agreed measure by the researcher & the teacher which is applying geometric treasure game in mathematic lesson on their logic mind, the result in first cycle becomes 70,30%, the second cycle is increasing until 88%. The amount of the increasing pre cycle to first cycle is 22, 50%, while the increasing to the second cycle is 17, 70%. The result has reached the indicator. The conclusion of this research shows that children's ability in especially in mathematic logic is increasing through the treasure game at TK Aisyiyah Bentangan Wonosari Klaten on 2015/2016 academic year.